The Influence of Zakat, Infak & Sedekah (ZIS) and Sukuk on Economic Growth - Salmin, La; Prehatin, Dian (EQUILIBRIUM, 2025)
This study aims to analyze the short-term and long-term effects of the distribution of Zakat, Infaq, and Sedekah (ZIS) funds and sukuk on economic growth in Indonesia. The results show that ZIS has a significant negative effect on economic growth in the long term and no effect in the short term. This finding indicates that the distribution of ZIS funds is still consumptive rather than productive. Conversely, sukuk has a significant positive effect in both the short and long term on economic growth, indicating that sukuk plays a significant role in financing productive sectors such as infrastructure and public development. These results emphasize the importance of optimizing the distribution of ZIS funds for productive activities and strengthening the use of sukuk as a sharia financing instrument to support sustainable economic growth in Indonesia.